Severe Thalassemia Bone Disease in a Young Woman with Transfusion-Dependent β-Thalassemia Major: Erlenmeyer Flask Deformity, Muscular Hemosiderin Deposition, and Profound Osteoporosis — A Case Report - Putu Arya Nugraha; Gede Kambayana; Pande Ketut Kurniari (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Beta-thalassemia major (β-TM) is a chronic transfusion-dependent hemolytic disorder in which thalassemia bone disease (TBD) is among the most frequent and least resolved long-term complications, driven by ineffective erythropoiesis with marrow expansion, iron-overload toxicity, and endocrine and nutritional deficiencies. Objective: To report a case of severe thalassemia bone disease in a young woman with transfusion-dependent β-TM and to highlight its diagnostic and therapeutic complexity. Case presentation: A 27-year-old woman with β-TM diagnosed at age two and a long history of iron overload presented with severe, movement-limiting right lower-limb pain, intermittent since 2019 and acutely worsened over the preceding month. She had documented hypersensitivity to deferasirox and was maintained on deferiprone. Examination showed clinical anemia, hepatosplenomegaly, and a painful, immobile right lower limb. Investigations confirmed hypochromic microcytic anemia (hemoglobin 5 g/dL), elevated ferritin, and low calcium and vitamin D. Pelvic radiography showed diffuse osteopenia; femoral radiography showed medullary widening with an Erlenmeyer flask deformity; and MRI revealed extensive hemosiderin deposition throughout the visualized bone and within the right rectus femoris muscle. DXA showed a lowest Z-score of −3.5, confirming profound low bone mineral density for age. Conclusion: This case highlights the diagnostic and therapeutic complexity of advanced TBD — structural deformity, soft-tissue iron deposition, and profound osteoporosis compounded by chelation-limited iron control — and underscores the need for an urgent, individualized, multidisciplinary approach.